If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 49 + -2x = 7x Solving 49 + -2x = 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 49 + -2x + -7x = 7x + -7x Combine like terms: -2x + -7x = -9x 49 + -9x = 7x + -7x Combine like terms: 7x + -7x = 0 49 + -9x = 0 Add '-49' to each side of the equation. 49 + -49 + -9x = 0 + -49 Combine like terms: 49 + -49 = 0 0 + -9x = 0 + -49 -9x = 0 + -49 Combine like terms: 0 + -49 = -49 -9x = -49 Divide each side by '-9'. x = 5.444444444 Simplifying x = 5.444444444
| 14x-8=x+19+8x+7 | | -x+y=-6 | | (5)/(6)*8+(3)/(4)=(11)/(12) | | 7x-15=7x+5 | | 10-8x=102-36x | | 13x-12=x+17+7x | | m+(15)=31 | | 3x+6=x+2+4x-7 | | 9x+1=10x-10+9x-7 | | 6x+7=5x-9 | | 3x-1=5+x+3 | | 5x+2=x+1+3x+4 | | 3x+3=4x-3+4 | | 8=2x+2+16x-12 | | Qs=4p-12 | | 13x-9=7x+5x+6 | | 13x-9=8x+5x+6 | | 3(5x-2)-6=3(3x+2) | | 6(m+4)+7(m+6)= | | 0.6(10x-8)-0.2(5x-4)=6 | | 17x+13=10x+20 | | 4n-6n=2 | | 8x^2-x-7=0 | | 3x^3-2x+3x-2=0 | | 5+x-3(x+4)=-18 | | 5n(18-4)n=-36 | | -[2x-(5+2)]=2+(2x+7) | | 7x*7x^2=28 | | (6x^2-5x+1)(x+1)= | | 4(3+n)=3(8+2n) | | 3x+x/2=3465 | | -1(2n+3)=-4n(2+3) |